(untitled) (Global Journal of Human-Social Science, 2015)
A study to assess the common factors leading to stress among adolescents in selected schools, Puducherry. A descriptive study was conducted and the objective of the study were to assess the level of stress among adolescent school-children, to identify common factors leading to stress among adolescents and to identify the association between demographic variables and stress. With assumption "Adolescent students will have stress" and the investigator proceeded on with the study. The study was conducted at various Government Higher Secondary Schools in and around Puducherry. Convenience sampling technique was used to obtain sample. The sample comprised of 500 adolescent students from eighth, ninth and tenth standard (boys and girls) of Government Higher Secondary Schools ’during the study period’. "The tool which was used for the study was Modified adolescent adjustment scale. The major findings of the study are many of the students were girls 69.6% (348). Majority of parents were unskilled workers 96.0% (480). 80.0% (400) student’s parent income was above 2000 per month. 50.6% (253) of the student belongs rural area and 49.4% (247) were belongs to urban area. The overall stress score among adolescent school children was 58.63%. 56.0% (280) had moderate level of stress. The adolescent students had more stress score in school and teacher related than other aspects of stress i.e., 72.88% and 62.50% respectively.